Emenda Constitucional 95/2016: instrumento de retomada da desvinculação das receitas da União sobre a Manutenção e Desenvolvimento do Ensino - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
The dissertation approaches the implementation of Constitutional Amendment (CA) 95, of December 15, 2016, which amended the Transitional Constitutional Provisions Act, establishing the New Fiscal Regime. It deals with the Federal Government's intervention, through CA 95/2016, in the financing of Education Maintenance and Development (EMD) under the responsibility of the Union. The research - theoretical and documentary - aims to unveil the requirements of CA 95/2016 for the funding policy of the Maintenance and Development of Union Education. The analysis of the historical materiality, which led to the approbation of CA 95/2016, revealed the maximum attention of the government to the maintenance of the political economy through the legislation, in compliance with the interests of a fraction of Brazilian society aligned with the impositions of international institutions, principally in the context of crisis and neoliberal intensification. The Investigation of the relationship between the financing of Brazilian education and CA 95/2016 has shown that this correlation is divergent, in contradiction with the education financing policies printed in the Federal Constitution, the Law of Guidelines and Bases for National Education and in the National Education Plan Act. The contradictions reveal that CA 95/2016 is a legal setback for education financing policy by unlink the Union's legally defined resources for the Maintenance and Development of Education and by retroacting financial achievements for the area. In this sense, the synthesis is that the 95/2016 Amendment, besides being an offensive, is the resumption of the project of a fraction of Brazilian society, aligned with the interests of international capital. In this context, it is revealed that, in this society project, the financing of public education is not a priority of the Brazilian state.
Constitutional Amendment 95/2016: resumption instrument for unleashing Union revenue on the Maintenance and Development of Education
Keywords: Direito constitucional - Emendas - Educação; Educação - Lei de Diretrizes e Bases da Educação Nacional - Lei do Plano Nacional de Educação; Subsídios governamentais - Educação; CIÊNCIAS HUMANAS: EDUCAÇÃO; Emenda Constitucional 95/2016; Financiamento da educação; Desvinculação; Manutenção e Desenvolvimento do Ensino